2018
DOI: 10.1111/pedi.12758
|View full text |Cite
|
Sign up to set email alerts
|

Cyclical variation in the incidence of childhood‐onset type 1 diabetes during 40 years in Navarra (Spain)

Abstract: The incidence of T1D in Navarre has increased 4-fold in the last four decades but is stable since 2001.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…This stabilisation and reduction of the incidence of T1DM in Ireland is similar to that of other high incidence countries 1–3,8 . Perhaps, the underlying environmental precipitants of T1DM in our population have passed or reached saturation and the incidence has reached its peak.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…This stabilisation and reduction of the incidence of T1DM in Ireland is similar to that of other high incidence countries 1–3,8 . Perhaps, the underlying environmental precipitants of T1DM in our population have passed or reached saturation and the incidence has reached its peak.…”
Section: Discussionsupporting
confidence: 74%
“…In Ireland, the highest rates of T1DM have been predominately in the older 10–14 year age category to date 4,9 . This trend was seen in a number of other high incidence countries, such as Norway, 2 Australia, 10 Spain 1 and Canada, 11 while others report the highest increases in children aged under 5 years, such as Poland, 6 Hungary 12 and Romania 13 . Recent research has shown that countries with a lower overall incidence rates of T1DM have had a faster rise in T1DM incidence particularly in children aged under 5 years 12,13 .…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…[94][95][96][97]100 Factors underlying geographical differences in the incidence of childhood T1D remain poorly understood. 101,102 Overall, there is no significant difference in the incidence of childhood T1D by sex, [103][104][105] although a slightly higher incidence has been reported in boys in some moderate-high incidence populations. 90,106 However, above the age of 15 years, there is a male preponderance in T1D incidence.…”
Section: Epidemiology Of Type 1 Diabetesmentioning
confidence: 95%
“…Overall, there is no significant difference in the incidence of childhood T1D by sex, 103–105 although a slightly higher incidence has been reported in boys in some moderate‐high incidence populations 90,106 . However, above the age of 15 years, there is a male preponderance in T1D incidence 107 …”
Section: Epidemiology Of Type 1 Diabetesmentioning
confidence: 99%